MODEL KESUKSESAN SISTEM INFORMASI PADA UKM TENUN SONGKET PALEMBANG - Marsudin, Yossy Tamara (Department of Information Systems, Institut Teknologi Sepuluh Nopember, 2018)
Songket is a typical cloth of Palembang city that symbolizes the glory of the kingdom of sriwijaya and the rapid maritime trade at that time. songket palembang is the best quality fabric in indonesia. Measuring the success of information technology system is needed as a form of evaluation for a company to continue to improve the quality of service, especially for Indonesia which is based on the field of small and medium enterprises (SMEs). This research was conducted to measure the success of information technology system at SMK Songket Palembang by using the variables that exist in Delone and McLean model. The variables used are system quality, information quality, service quality, use and net benefit and use perceived usefulness variables in TAM model. This study was conducted for 8 months. The population of the study were employees of SMEs Songket Palembang and the samples were 90 employees. The results obtained are System quality and service quality has no effect on the use of Information quality while and perceived usefulness affect the use and Use effect on net benefits.   Songket merupakan kain khas Kota Palembang yang melambangkan kejayaan Kerajaan Sriwijaya dan pesatnya perdagangan maritim pada saat itu. Songket Palembang memiliki kualitas kain terbaik di Indonesia. Pengukuran kesuksesan sistem teknologi informasi sangat dibutuhkan sebagai bentuk evaluasi bagi suatu perusahaan untuk terus meningkatkan mutu pelayanan, terlebih bagi Indonesia yang bertumpu pada bidang usaha kecil dan menengah (UKM). Penelitian ini dilakukan untuk mengukur kesuksesan sistem teknologi informasi pada UKM Songket Palembang dengan menggunakan variabel yang ada pada model Delone dan McLean, yaitu variabel system quality, information quality, service quality,  use dan net benefit serta menggunakan variabel perceived usefulness yang ada pada model TAM. Penelitian ini dilakukan selama 8 bulan. Populasi penelitian adalah para pegawai UKM Songket Palembang dengan sampel sebanyak 90 pegawai. Hasil penelitian yang didapat adalah system quality dan service quality tidak berpengaruh yang terhadap use sedangkan Information quality dan perceived usefulness berpengaruh terhadap use dan Use berpengaruh terhadap net benefit.